Study of electrochemical phosphate sensing systems: Spectrometric, potentiometric and voltammetric evaluation - Kivlehan, F.; Mace, W.; Moynihan, H.; Arrigan, Damien (Pergamon-Elsevier Science Ltd, 2009)
Characterization of the interaction of a urea-functionalized calix[4]arene ionophore and phosphate wasundertaken by combination of nuclear magnetic resonance (NMR) spectrometry, potentiometric selectivity coefficient evaluation and voltammetric ion transfer at the interface between two immiscibleelectrolyte solutions (ITIES). NMR revealed that the urea protons were involved in complexation withthe target anion and potentiometric separate solution selectivity data indicated selectivity for phosphateover chloride and sulphate. Voltammetry at the ITIES confirmed that the ionophore-facilitated transfer ofmonohydrogen phosphate occurred in preference to dihydrogen phosphate transfer. The results correlatewith previously reported data on the potentiometric evaluation of this calixarene as an anionophore inPVC-membrane electrodes. The data provide the basis for development of amperometric monohydrogenphosphate sensors based on the ion-transfer principle.